AB0448 Vitamin d level is decreased in patients with takayasu's arteritis, but is unassociated with the presence of fibromyalgia. (23rd January 2014) - Alibaz-Oner, F.; Asmaz-Haliloglu, O.; Gogas-Yavuz, D.; Can, M.; Direskeneli, H.
Abstract : Background: Takayasu arteritis (TAK) is a chronic, large-vessel arteritis predominantly affecting aorta, its major branches and the pulmonary arteries. Vitamin D, as a steroidal hormone, has recently been shown to have immunoregulatory and immunosuppressive effects. Low vitamin D levels are demonstrated in various autoimmune disorders. Objectives: The association between Vitamin D deficiency and non-specific musculoskeletal pain, including fibromyalgia (FM) syndrome, is also controversial. The aim of this study is to investigate vitamin D levels in patients with TAK and to investigate the association between fibromyalgia and vitamin D deficiency in this group. Methods: The study included 36 patients with TAK and 30 age and sex-matched healthy control subjects. Plasma 25-hydroxy vit D [25(OH) vit D] levels were measured with HPLC. "Deficiency" was defined as 25(OH) vit D level below 25 nmol/ liter and "insufficiency" as below 50 nmol/liter. All patients were examined for FM tender points and asked to complete new ACR 2010 FM questionnaire for FM. Results: Plasma 25(OH) vitamin D were significantly lower in TAK patients (16.93±10.62 nmol/liter) than healthy controls (64.63±21.82 nmol/liter). The frequency of vitamin D deficiency was 83.3% in patients with TAK compared to 3.3% in controls. Plasma 25(OH) vit D levels were similar between clinically active and inactive patients. No association was also observed between vitamin D levels and the presence of FM (p=0.263 for 1990 Criteria, p=0.789 for ACR-2010 Criteria). Conclusions: We observed a high prevalence of Vitamin D deficiency in patients with TAK, however without any association with the presence of FM. Vitamin D deficiency can be a predisposing factor for immune activation and we suggest monitorization and replacement of Vitamin D status in all TAK patients. Disclosure of Interest: None Declared